Are We Walking the Talk? Questions of Structure and Agency in the Research on Teaching in Adult Education - John M. Dirkx; Jennifer Kushner; Susan B. Slusarski (Adult Education Research Conference, 2000)
Despite current prevalence of constructivist epistemologies, the practice of teaching adults continues to reflect representational approaches to meaning. In this roundtable discussion, we explore the use of Giddens’ theory of structuration as a framework for deepening our understanding of the lack of change in teaching.